To own or not to own: How ownership affects user innovation - An empirical study in the German rowing community - Frank Tietze; Thorsten Pieper; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2013)
Prior research on user innovation has concentrated on markets in which products (e.g., mountain bikes, kitesurfing equipment, tools, etc.) are typically purchased by those users who modify them. However, in numerous markets, this is not the case, for example, those in which equipment is rented. Moreover, firms increasingly servitize, selling functionality instead of products. Thus, product ownership is being transferred to users less and less. Instead of purchasing products, users increasingly rent or lease equipment. Consequently, our research investigates the impact of product ownership on user innovation behavior. We question whether absent ownership is an innovation barrier, negatively impacting users' propensity to innovate. This should be particularly relevant to firms that collaborate with users, scouting for their ideas. This study was conducted in the German rowing community. In contrast with previously studied sports markets, equipment ownership in rowing often remains with sport clubs and not with individual users. Following a pre-study, we distributed a survey to the members of 410 clubs enlisted in the German Rowing Federation's roster. Our approach yielded 743 responses. We present results from multivariate ordinal and logistic regressions for two dependent variables (idea generation and realized ideas), differentiating between three ownership types (private, non-private with dedicated use, and non-private with shared use). Our results reveal that private ownership has significant positive effects on user innovation behavior. Users, who own their equipment develop significantly more innovative ideas and have a significantly higher probability to realize ideas than users who use equipment that is owned by a third party. We find that private ownership positively moderates use experience's impact on the development and realization of ideas. The results imply that manufacturers should be aware of the effect that ownership could have, particularly when offering services or in situations where ownership rights are not transferred to users (e.g., leasing models). We discuss measures to remedy the negative impact of absent ownership, such as equipment sponsorships complemented by specific use contracts, experiment labs, and insurances.
Keywords: 650